5 questions to Frances Riu, creator of the Escola Cristiana de Catalunya (Journal of Parents and Teachers, 2013)
In this interview we are approaching Frances Riu, a religious salesiano who managed the “Escola Cristiana de Catalunya” between 1976 and 2005. The questions, focused on the educative aspect, are about his biography and his opinion about actual aspects.
Keywords: Interview; Francesc Riu; educator; education.